2009
DOI: 10.5194/angeo-27-1413-2009
|View full text |Cite
|
Sign up to set email alerts
|

Features of auroral breakup obtained using data of ground-based television observations: case study

Abstract: Abstract. The knowledge about the relative timing of events during the substorm expansion phase onset is very important for understanding the physics of substorms. In this work ground-based television (TV) imaging technique was used for observations of the first auroral arc brightening near zenith of TV chamber for the case of an isolated substorm. The method of the TV image filtration was used giving the possibility to analyze motion of sub visual auroral arcs. The analysis of the connection between the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
2
6
0
1
Order By: Relevance
“…Localization of an isolated substorm expansion onset is one of the main endeavors of the THEMIS satellite mission. Lui et al (2008) have found that the onset is localized at the geocentric distances <10 R E , confirming previous results (see also the discussion in the paper Antonova et al, 2009a).…”
Section: Introductionsupporting
confidence: 80%
“…Localization of an isolated substorm expansion onset is one of the main endeavors of the THEMIS satellite mission. Lui et al (2008) have found that the onset is localized at the geocentric distances <10 R E , confirming previous results (see also the discussion in the paper Antonova et al, 2009a).…”
Section: Introductionsupporting
confidence: 80%
“…Our results are consistent with this suggested process for substorm expansion onset. Also, Antonova et al [2009] suggested that a gradual auroral enhancement as found here might lead to an electrostatic instability within the inner plasma sheet. It is also worth noting that pressure angular data (not shown) shows an enhancement of parallel pressure giving a field‐aligned anisotropy > at THE for three of the five events, and at THD for one of the five events, in association with the spatial pressure gradient enhancement.…”
Section: Summary and Discussionmentioning
confidence: 55%
“…[26] The increase in the values of diffusion coefficients with the distance in the tailward direction also can help to explain why the substorm onset takes place deeply inside the magnetosphere, as confirmed by many authors [see, e.g., Samson et al, 1992aSamson et al, , 1992bFrank and Sigwarth, 2000;Lyons et al, 2002;Stepanova et al, 2002;Yahnin et al, 2002;Dubyagin et al, 2003;Antonova et al, 2009], because only the region which was stable before the onset of the substorm expansion phase can become unstable.…”
Section: Discussionmentioning
confidence: 82%